An Integrated Regulatory Network of mRNAs, microRNAs, and lncRNAs Involved in Nitrogen Metabolism of Moso Bamboo - Yuan, Tingting; Zhu, Chenglei; Li, Guangzhu; Liu, Yan; Yang, Kebin; Li, Zhen; Song, Xinzhang; Gao, Zhimin (Frontiers in Genetics, 2022)
Nitrogen is a key macronutrient essential for plant growth and development, and its availability has a strong influence on biological processes. Nitrogen fertilizer has been widely applied in bamboo forests in recent decades, however, the mechanism of nitrogen metabolism in bamboo is not fully elucidated. Here, we characterized the morphological, physiological and transcriptome changes of moso bamboo in response to different schemes for nitrogen addition to illuminate the regulation mechanism of nitrogen metabolism. Appropriate nitrogen addition improved the chlorophyll content and Pn (net photosynthetic rate) of leaves, the nitrogen and ammonium contents of the seedling roots, the biomass of the whole seedling as well as the number of lateral roots, and the activity of enzymes involved in nitrogen metabolism in roots. Based on the whole transcriptome data of roots, a total of 8,632 DEGs (Differentially Expressed mRNAs) were identified under different nitrogen additions, including 52 nitrate transporter genes, six NR (Nitrate Reductase) genes, two NiR (Nitrite Reductase) genes, two GS (Glutamine Synthase) genes, two GOGAT (Glutamate Synthase) genes, three GDH (Glutamate Dehydrogenase) genes, and 431 TFs belonging to 23 families. Meanwhile, 123 DEMs (Differentially Expressed miRNAs) and 396 DELs (Differentially Expressed lncRNAs) were characterized as nitrogen responsive respectively. Furthermore, 94 DEM-DEG pairs and 23 DEL-DEG pairs involved in nitrogen metabolism were identified. Finally, a predicted regulatory network of nitrogen metabolism was initially constructed including 17 nitrogen metabolic pathway genes, 15 TFs, four miRNAs and 10 lncRNAs by conjoint analysis of DEGs, DEMs, DELs and their regulatory relationship which was supported by RNA-seq data and qPCR results. The lncRNA-miRNA-mRNA network provides new insights into the regulation mechanism of nitrogen metabolism in bamboo, which facilitates further genetic improvement for bamboo to adapt to fluctuating nitrogen environment.